슈퍼 오스테나이트계 스테인리스강의 소성 변형률에 따른 부식특성 평가 - 고대환(Dae-Hwan Ko); 신용택(Yong-Taek Shin) (대한용접·접합학회지, 2018)
In this study, corrosion properties of UNS S32654 (654SMO), which is a kind of super austenitic stainless steel, were evaluated according to the change of strain. Strain of base metal was applied from 0% to 57%, and then microstructure evaluation, CPT, CCT and polarization tests were performed. As a result of microstructure, it was confirmed that the slip was increased as the strain increased. CPT of all strain ranges was 90 ℃ or more, and the CCT was from 80 ℃ to 90 ℃, respectively. In the polarization test, it was difficult to find the change of the corrosion potential according to the change of the strain, and it was confirmed that plastic induced martensitic phase which could be generated by the deformation in the austenite stainless steel was not occurred by XRD. Finally, it was confirmed that there was no difference in the corrosion resistance characteristic of 654SMO steel according to the strain change KCI Citation Count: 0